Methods for the destruction of oxalic acid decontamination effluents - Blenkinsop, Jessica; Rivonkar, Aditya; Robin, Mathurin; Carey, Thomas; Dunnett, Barbara; Suzuki-Muresan, Tomo; Percin, Cavit; Abdelouas, Abdesselam; Street, Jonathan (Frontiers in Nuclear Engineering, 2024)
Oxalic acid is encountered within industrial processes, spanning from the nuclear sector to various chemical applications. The persistence and potential environmental risks associated with this compound underscore the need for effective management strategies. This article presents an overview of different approaches for the destruction of oxalic acid. The study explores an array of degradation methodologies and delves into the mechanistic insights of these techniques. Significant attention is channeled towards the nuclear industry, wherein oxalic acid arises as a byproduct of decontamination and waste management activities. An integral aspect of decommissioning efforts involves addressing this secondary waste-form of oxalic acid. This becomes imperative due to the potential release of oxalic acid into waste streams, where its accommodation is problematic, and its capacity to solubilize and transport heavy metals like Pu is a concern. To address this, a two-tiered classification is introduced: high concentration and low concentration scenarios. The study investigates various parameters, including the addition of nitric acid or hydrogen peroxide, in the presence of metallic ions, notably Mn2+ and Fe2+. These metallic ions are common components of effluents from metallic waste treatment. Additionally, the impact of UV light on degradation is explored. Investigations reveal that at high concentrations and with the influence of hydrogen peroxide, the presence of metallic cations accelerates the rate of destruction, demonstrating a direct correlation. This acceleration is further enhanced by exposure to UV light. At low concentrations, similar effects of metallic cations are observed upon heating the solution to 80°C. The rate of destruction increases proportionally with hydrogen peroxide concentration, with an optimal oxalic acid to hydrogen peroxide ratio of 1:100. Interestingly, a low-power UV light exerted no discernible effects on the destruction rate; heating alone proved sufficient. In essence, regardless of concentration, the degradation of oxalic acid with hydrogen peroxide experiences acceleration in the presence of metallic ions such as Mn2+ and Fe2+.